Konsep Dasar Administrasi Sarana dan Prasarana Pendidikan Berbasis Teknologi di Era Society 5.0 - Adilah Filzhah; Linda Amalia; Ahmad Sabri; Rully Hidayatullah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The trend of thinking about education suggests that, educational paradigm based on standards were discussed more and more, acknowledged and appreciated. This trend started from the realization that education need a reference of quality for each of the organizers and the educational unit which is called the National Education Standards (SNP). Indicator of education quality obtained through the filled based on eight ational Education Standards (SNP). Management of facilities and infrastructure were declare based on policy from Permendiknas No.19 in 2007. The data collection technique in this study was carried out by triangulation which was carried out using observations, interviews and documentation from the same source. While the data analysis techniques used are data collection, data reduction, data display, and drawing conclusions. The main objective is to create an effective, inclusive, and supportive learning environment that promotes the holistic development of each student. Some of the principles of student management include goals that are aligned with school management, activities that support educational goals, building student unity, good mentoring, and encouraging student independence. The scope of student management includes analysis of student needs, student recruitment, student selection, student orientation, student grouping, student leadership and development, and registration and reporting. This document also discusses the importance of understanding the characteristics of each student, creating a safe and comfortable learning environment, facilitating effective learning, encouraging active participation, building positive relationships, developing social skills, leadership, and supporting students' holistic development. Based on the previous research has found many gaps related with this context. However, there was no studies have evaluated the mechanism of facilities and infrastructure as a whole and systematically according to grant theory. These mechanisms include the supply, distribution, use and maintenance, inventory, and elimination of school facilities and infrastructure.